Point-contact Andreev-reflection spectroscopy in anisotropic superconductors: the importance of directionality (Review Article) - Daghero, D.; Tortello, M.; Pecchio, P.; Stepanov, V.A.; Gonnelli, R.S. (Физика низких температур, 2013)
Point-contact Andreev-reflection spectroscopy (PCARS) has demonstrated to be one of the most effective experimental
tools for the investigation of fundamental properties of superconductors such as the superconducting
gap and the electron–phonon (or, more generally, electron–boson) coupling. By reviewing relevant examples reported
in literature and presenting new results, in this paper we show that when the direction of the interface with
respect to the crystallographic axes can be controlled (as in single crystals and epitaxial films) PCARS can provide
invaluable information about the anisotropy of the pairing wavefunction or — in the case of multiband superconductors
— on the number, amplitude and symmetry of the energy gaps. Moreover, the analysis of PCARS
results within a suitable 3D generalization of the BTK model allows obtaining qualitative information about the
topology of the Fermi surface.